PENGARUH PENERAPAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PENDEKATAN SAINTIFIK TERHADAP HASIL BELAJAR SISWA PADA MATERI SISTEM KOORDINASI KELAS XI DI SMA NEGERI 1 SEKAMPUNG - Eva Yuliana; Ratini Ratini; HRA Mulyani (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2023)
The aims of this study was to determine the effect of LKPD based on a scientific approach on cognitive learning outcomes and which one is higher between the average cognitive learning outcomes of the Coordination System Biology using LKPD based on a scientific approach and those without using LKPD. The research method used is a quasi-experimental research method (Quasy Experiment). The experimental design used was the Test-Only control design, namely this design has 2 groups, the first group is the experimental class group and the control class group. The sample in this study was obtained by cluster random sampling, random sampling was obtained by drawing, namely class XI MIPA-1 as the control class and MIPA-2 as the experimental class. The instrument in this study was a test with a total of 17 questions. Based on the research results, it can be seen that the average value of the experimental class is 86.44 and the average value of the control class is 70.88. Based on the results of hypothesis testing using two-party t-test obtained –t1 - < t1 t1 (-2,00< 28,93 > 2,00) means that learning outcomes in the experimental class using LKPD are not the same as learning outcomes in the control class that do not use LKPD. Then based on the hypothesis test using one-party t-test results obtained -tdaf<thit (-1.67 <28.41) means that the learning outcomes of the experimental class using LKPD are greater than the learning outcomes of the control class that do not use LKPD in SMA Negeri 1 Sekampung.